Prevalence and Related Factors of Lower Urinary Tract Infection in Frail Older Adults Undergoing Major Noncardiac Surgery - Warin Thangrom; Inthira Roopsawang; Suparb Aree-Ue (Geriatrics, 2023)
Urinary tract infections are the most common complication after surgery in older adults, resulting in poor operative outcomes and reduced quality of life after discharge. However, there is limited research investigating the relationships between urinary tract infection and associated factors in frail older surgical patients, particularly in Thailand. This retrospective study included 220 frail older patients aged ≥ 60 years who had undergone major noncardiac surgery at a tertiary care hospital in Thailand from January 2015 to December 2019. The sample was recruited using the criteria indicated in the modified Frailty Index-11 and having the blood glucose level determined within 2 h before surgery. The prevalence of lower urinary tract infections was 15% post-surgery. Firth’s logistic regression analysis revealed that the equation could predict the accuracy of lower urinary tract infections by 88.5%. Frailty, blood glucose levels, complication during admission, and personal factors together predicted the variability of lower urinary tract infections. Adjusting for other variables, being an older adult with severe frailty and complications during hospital admission significantly increased the risk of developing lower urinary tract infections (odds ratio = 3.46, p < 0.05; odds ratio = 9.53, p < 0.001, respectively).